Technical-economical-environmental assessment of grid-connected hybrid renewable energy power system for Gaza Strip-palestine - Hala J. El‐Khozondar; Rifa J. EL-Khozondar; Yasser F. Nassar; Fady El-Batta (Engineering Science and Technology, an International Journal)
The Gaza Strip, located in Palestine, suffers from chronic energy shortages caused by ongoing political instability, which has severely damaged its electricity infrastructure. This study explores the feasibility of integrating high levels of renewable energy into Gaza’s power system via a hybrid on-grid configuration. The research aligns with UN SDG-7, aiming to provide affordable, clean energy to all nations, and evaluates multiple criteria, including economic, environmental, energy security, and technical factors. Using the Hybrid Optimization of Multiple Energy Resources (HOMER) simulation tool, various grid-connected scenarios were assessed to minimize the Levelized Cost of Energy (LCOE), Net Present Cost (NPC), and greenhouse gas (GHG) emissions. The findings reveal an optimized hybrid energy system comprising photovoltaic (PV) panels, wind turbines, a biomass generator, a geothermal generator, and a sea wave (hydropower) system. The energy contribution from each source is as follows: 48.5 % from PV, 23.2 % from wind, 19.5 % from hydropower, 0.34 % from biogas, 0.0233 % from geothermal, and 8.44 % from grid purchases. Notably, 45.6 % of the system’s electricity can be sold back to the utility grid. The system reaches a peak capacity of 2,190.208 MW and meets a daily consumption of 17,874.430 MWh, while reducing annual fuel consumption from 1,311 m3 to 672 m3. Economically, the system achieves a Levelized Cost of Energy of $0.034/kWh, with a Net Present Cost of $2.86 billion, annual savings of $358 million, and a payback period of 6 years. Environmentally, the system cuts CO2 emissions by 52 %, reducing emissions from 703,264 tonnes/year to 399,872 tonnes/year, highlighting its strong sustainability potential. This study represents the first comprehensive application of HOMER to design a renewable energy system capable of supplying the entire urban load in Gaza, expanding on previous efforts that were limited to rural or remote areas.